Keanekaragaman Vegetasi dan Pola Persebaran Pohon di Mata Air Kalisegoro 2 Kecamatan Gunungpati - Alfathqi, Rheza Rizky; Julpa, Ira Sopiana; Mauliya, Durrotul Jahroo; Ni’matuzzahroh, Ni’matuzzahroh; Hartanto, Naufal; Haris, Amnan; Fariz, Trida Ridho; Jabbar, Abdul (ORGANISMS: JOURNAL OF BIOSCIENCES, 2024)
Human life on earth cannot be separated from water. Water is an absolute necessity that humans need. Water needs can be obtained from 2 sources, namely water from the surface and water from the ground. Springs are a source of water obtained from groundwater. Kalisegoro 2 spring is one of the springs in Gunung Pati District, Semarang City. This spring is in Kalisegoro Village where the surrounding land cover is vegetation. This type of research is quantitative in the form of analysis of species diversity and tree distribution patterns. The aim of this research is to determine the diversity of tree species and tree distribution patterns in Kalisegoro 2 springs in Gunung Pati District. The results of this research show that the diversity of vegetation in the Kalisegoro 2 springs amounts to 145 individuals and 10 types of species, the Swietenia mahagoni species is the dominant species found at the Kalisegoro 2 springs location with an INP of 0.59. The vegetation diversity index at Kalisegoro 2 springs is included in the medium category in the range 1<H'<3. The distribution pattern of trees in the Kalisegoro 2 spring is quite even, this is known through the tracking method that has been carried out in the area around the spring. ABSTRAKKehidupan manusia di muka bumi tidak dapat terlepas dari air. Air merupakan suatu kebutuhan mutlak yang dibutuhkan oleh manusia. Kebutuhan air dapat diperoleh melalui 2 sumber yakni air dari permukaan dan air tanah. Mata air merupakan salah satu sumber air yang bersumber dari air tanah. Mata air Kalisegoro 2 merupakan salah satu mata air yang berada di Kecamatan Gunungpati Kota Semarang, mata air ini terdapat di Kelurahan Kalisegoro yang tutupan lahan sekitarnya berupa vegetasi. Jenis penelitian ini adalah kuantitatif berupa analisis keanekaragaman jenis dan pola penyebaran pohon. Tujuan dari penelitian ini adalah untuk mengetahui keanekaragaman jenis pohon dan pola persebaran pohon di sekitar mata air. Hasil penelitian ini menunjukkan keanekaragaman vegetasi di mata air kalisegoro 2 berjumlah 145 individu dan 10 jenis spesies, spesies Swietenia mahagoni merupakan spesies dominan yang ditemukan di lokasi mata air Kalisegoro 2 dengan jumlah INP sebesar 0,59. Indeks keanekaragaman vegetasi pada mata air Kalisegoro 2 termasuk dalam kategori sedang karena berada pada rentang 1<H'<3. Pola persebaran pohon pada mata air Kalisegoro 2 sudah cukup merata, hal ini diketahui melalui metode tracking yang telah dilakukan di area sekitar mata air.